2007
DOI: 10.1016/j.cell.2007.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Sensory-Neurosecretory Cell Types in Annelid and Fish Forebrain: Insights into Hypothalamus Evolution

Abstract: Neurosecretory control centers form part of the forebrain in many animal phyla, including vertebrates, insects, and annelids. The evolutionary origin of these centers is largely unknown. To identify conserved, and thus phylogenetically ancient, components of neurosecretory brain centers, we characterize and compare neurons that express the prohormone vasotocin (vasopressin/oxytocin)-neurophysin in the developing forebrain of the annelid Platynereis dumerilii and of the zebrafish. These neurons express the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
368
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(398 citation statements)
references
References 68 publications
21
368
0
Order By: Relevance
“…However, during the course of evolution, the mammalian pinealocyte has lost the photoreceptive and pacemaker functions and acts primarily as an endocrine organ that secretes melatonin. It has been proposed that multifunctionality (for example, sensory and neurosecretory functions) is a general feature of ancient cell types (Vigh's protoneuron concept) [32][33][34] . Over the course of evolution, these multiple functions were then inherited in a complementary manner by sister cell types with increasing specialization.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the course of evolution, the mammalian pinealocyte has lost the photoreceptive and pacemaker functions and acts primarily as an endocrine organ that secretes melatonin. It has been proposed that multifunctionality (for example, sensory and neurosecretory functions) is a general feature of ancient cell types (Vigh's protoneuron concept) [32][33][34] . Over the course of evolution, these multiple functions were then inherited in a complementary manner by sister cell types with increasing specialization.…”
Section: Discussionmentioning
confidence: 99%
“…S3A) showed that the axonal projections of these cells terminate in the apical nerve plexus ( Fig. 2 E and F), a region of strong neurosecretory activity (18,19). By using the Platynereis MIP antibody or an antibody against the conserved C-amidated dipeptide VWamide that is strongly conserved in mollusks and annelids (Figs.…”
Section: Mip Triggers Larval Settlement In Platynereismentioning
confidence: 99%
“…We scanned, registered, and averaged at least five individual larvae per gene from whole-mount in situ hybridization samples. We analyzed the neurosecretory marker prohormone convertase prohormone convertase 2 (phc2) and the neuroendocrine transcription factors orthopedia (otp) (18) and dimmed (dimm) (Fig. S4 A-D).…”
Section: Mip Triggers Larval Settlement In Platynereismentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, the annelid P. dumerilii has become a valuable model for evolutionary developmental biology studies, especially regarding the development of its nervous system that resembles that of vertebrates in many aspects. Studies in Platynereis shed light on several ancestral features of the CNS in bilaterians 13 , including the molecular regionalization of the neurectoderm along the mediolateral axis 14 , the presence of conserved brain neurosecretory cells 15 , and the common ancestry of the vertebrate pallium and the protostome corpora pedunculata 16 .…”
mentioning
confidence: 99%